2019
DOI: 10.14254/2071-789x.2019/12-4/16
|View full text |Cite
|
Sign up to set email alerts
|

Confident millennials: Differences in consumer confidence across five generations

Abstract: This paper investigates if individuals experiencing different socioeconomic environments during their formative years have different expectations about future economic conditions. We use Swedish survey data to analyse differences in expectations across five generations of consumers by testing if they have different levels of confidence. The paper focuses on all the different generations of the 1900s as defined by Howe and Strauss (1997, 2000). In our econometric model, we use the Millennial Generation as a bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“…According to the generational theory, Generation Z, also called Baby Bloomers or iGeneration, includes individuals born between 1994 and 2010 (Williams and Page 2011;Persson 2019). Outnumbering Millennials (Gen Y) by more than one million, Generation Z members or the iGeneration (Vasiliu et al 2016;Jacobsen 2017;Velčovská 2018) make up the most attractive segment for producers and retailers.…”
Section: The Sustainable Orientation Of Generation Zmentioning
confidence: 99%
“…According to the generational theory, Generation Z, also called Baby Bloomers or iGeneration, includes individuals born between 1994 and 2010 (Williams and Page 2011;Persson 2019). Outnumbering Millennials (Gen Y) by more than one million, Generation Z members or the iGeneration (Vasiliu et al 2016;Jacobsen 2017;Velčovská 2018) make up the most attractive segment for producers and retailers.…”
Section: The Sustainable Orientation Of Generation Zmentioning
confidence: 99%
“…Similarly, students older than 22 years who reported a higher confidence level may have more life experience and could have been exposed to prior working opportunities in the accountancy field. According to the literature, Generation Z and Millennials (Moore et al 2017;Persson 2019;Duger 2021) types of students are characterised by being confident and to easily adapt to change, but it seems like students' confidence levels to cope with their studies and to actively engage with their academic instructors under Covid-19 conditions are resonating close to "uncertainty" and the level of only being "slightly confident".…”
Section: Results Of the Factor Analysismentioning
confidence: 99%
“…The study by Duger (2021) determined the effect of individualism and collectivism cultural tendencies and selfconfidence levels of Generation Z on 297 university students on their motivation to lead and concluded that self-confidence has a significant and positive effect on social-normative leadership motivation. The study by Persson (2019) investigated the confidence levels across generations and found that confidence increases gradually across generations with the Millennials being more confident than previous generations.…”
Section: Age/generation Z and Millennialsmentioning
confidence: 99%
“…Today, the generations are divided into six groups according to age characteristics [3,5,[19][20][21][22] It should be noted that there is no consensus among researchers about the age distribution of generations [23,24]. In particular, the starting year for Gen Z (also known as i-Generation; centennials; zoomers [21]) is sometimes considered to be 1990 [25], while the years 1991 [26], 1994 [27,28] and 1995 [29] are also accepted as the starting year. There are even those who accept the beginning of Generation Z as 1997.…”
Section: Introductionmentioning
confidence: 99%